From HPV-positive towards HPV-driven oropharyngeal squamous cell carcinomas. (January 2016) - Boscolo-Rizzo, Paolo; Pawlita, Michael; Holzinger, Dana
Abstract : Highlights: In the era of de-escalation trials, the identification of HPV-driven OPSCC is essential. HPV-DNA or p16 IHC are the most used tests to define the HPV status in OPSCC. HPV-DNA or p16 IHC as stand-alone tests suffer from poor accuracy. A broad panel of different markers is now available to detect HPV-driven tumors. Clinicians should be aware of proper diagnostic tools in detecting HPV-driven tumors. Abstract: The incidence of HPV-positive oropharyngeal squamous cell carcinoma (OPSCC), which is both biologically and clinically distinct from tobacco- and alcohol-related OPSCC, is dramatically increasing. The finding that individuals with HPV-positive local/regionally advanced OPSCC have a significantly better prognosis than their negative counterparts have led to efforts to de-escalate treatment in those patients to avoid serious side effects and to improve their long-term quality of life, while maintaining treatment efficacy. Identifying diagnostic tests that are able to distinguish cancers etiologically associated with HPV is thus becoming a pressing challenge for researchers. The purpose of this review is to provide an overview of the diagnostic tools presently available to evaluate HPV status in patients with OPSCC and, in particular, to discuss their strengths and weaknesses in identifying those infections that are the real driving force in the oropharyngeal carcinogenesis process.